Urban Pastoral: Tradition and Innovation in Apollinaire's "Zone" and Rilke's "Zehnte Duineser Elegie" - Eleanor E. ter Horst (Studies in 20th & 21st Century Literature, 2008)
Two early twentieth-century poets, Rainer Maria Rilke and Guillaume Apollinaire, create new relationships to literary traditions and thus reconfigure the meanings of modernity. In Apollinaire's "Zone" and Rilke's "Tenth Duino Elegy," the city represents what is most distincively modern and revolutionary about poetic practice, yet it also provides a link to the literary and historical past. The city in these poems is a site of poetic potentiality, where time is no longer characterized by the rigid separation between past and present, and where space is not geograpically delineated. Through the poets' use of metaphor and apostrophe, which create a suspension of time and space, the city becomes a vehicle for the exploration of æsthetic issues, such as the relationship between tradition and innovation in poetic practice. The modern, urban setting of these poems suggests a break with the past, while their repeated references to classical elegy and the pastoral contradict this conception of the modern. Neither rejecting the past nor situating themselves in a linear tradition of poetic descent, both poems point to new models of literary creation, which redefine the poets' relationships with their literary antecedents.
Keywords: Rainer Maria Rilke; Guillaume Apollinaire; modernity; Zone; Tenth Duino Elegy; poetry; city; time; past; present; space; tradition; innovation; classical elegy; pastoral; urban